Heart-Lung interaction in spontaneous breathing subjects: the basics - Magder, Sheldon (Ann Transl Med, 2018)
Heart-lung interactions occur primarily because of two components of lung inflation, changes in pleural pressure and changes in transpulmonary pressure. Of these, changes in pleural pressure dominate during spontaneous breathing. Because the heart is surrounded by pleural pressure, during inspiration the environment of the heart falls relative to the rest of the body. This alters inflow into the right heart and outflow from the left heart. Alterations in transpulmonary pressure can alter the outflow from the right heart and the inflow to the left heart. These interactions are modified by the cardiac and respiratory frequency, ventricular function and magnitude of the respiratory efforts.